A contribution to the petrology of kimberlites - Kruger, Floris Johan (Rhodes University, Faculty of Science, Department of Geology, 1978)
The petrogenetic relationships of the different varieties of kimberlite in the De Beers Mine and Letseng-Ia-terai composite diatremes have been investigated using petrographic and chemical methods. Kimberlites in the Letseng-Ia-terai diatreme were found to be strongly contaminated by crustal material, mainly basalt. A method to correct for the effects of the contamination has been developed and applied to these kimberlites. Using the corrected data, the four kimberlite types in each group appear to be related to each other by crystal/liquid fractionation models. However the two groups cannot be related to each other. The De Beer Mine has two varieties of kimberlite, a monticellite apatite and calcite rich variety which intruded first, and a phlogopite rich type forming a discrete cylindrical body within the earlier kimberlite. These two kimberlites do not appear to be related by any of the fractionation models discussed. An examination of the data from this work and published sources, suggests that kimberlites are derived from below the low velocity zone by small degrees of partial melting involving garnet lherzolite with subordinate phlogopite and carbonate. Diamonds are probably incorporated as xenocrysts in the magma. Upward movement and emplacement of kimberlite appears to have been very rapid. The diatremes were probably eroded and shaped by gas, derived from the kimberlite magma, escaping to surface along weak zones in the earth's crust. Xenoliths of crustal material incorporated in the kimberlite on intrusion have also been studied and various features due to alteration by the magma are described, including the formation of natrolite and cebollite. The latter is a rare mineral that has not been described from kimberlite before.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Kimberlite -- Africa, Southern; Petrology; Igneous rocks -- Inclusions